Tamarix articulata Induced Prevention of Hepatotoxicity Effects of In Vivo Carbon Tetrachloride by Modulating Pro-Inflammatory Serum and Antioxidant Enzymes to Reverse the Liver Fibrosis - Abdullah M. Alnuqaydan; Abdulmajeed G. Almutary; Mohammed A. Alsahli; Sulaiman Alnasser; Bilal Rah (MDPI AG, 2022)
This study evaluates the hepatoprotective activity of a Tamarix articulata extract against carbon tetrachloride-mediated hepatotoxicity in Wistar rats. Our results demonstrated that the oral administration of Tamarix articulata extract (50 mg/kg b.w.) significantly restored the serum levels of liver enzymes and antioxidant parameters (superoxide dismutase, catalase, glutathione reductase, and thiobarbituric reactive substances). Histopathology analysis revealed that Tamarix articulata extract significantly reduced hepatic fibrosis by inhibiting the necrosis of hepatocytes. Furthermore, serum pro-inflammatory (tumor necrosis factor-alpha, tumor growth factor-beta, and interleukin-6) markers were significantly restored. However, the anti-inflammatory cytokine adiponectin levels increased to normal levels in the group treated with Tamarix articulata extract. Additionally, we observed diminished reactive oxygen species production and the depolarization of mitochondrial membrane potential in hepatocytes extracted from animal livers treated with Tamarix articulata extract. Our findings suggest that Tamarix articulata extract prevents liver fibrosis induced by carbon tetrachloride and decreases the necrotic population of hepatocytes. These events restored the antioxidant enzymatic activity, serum levels of liver enzymes, and pro-inflammatory markers to their normal levels.